Evaluation of maternal performance about food security in dietary diversity for children aged 12-24 months and its relationship with anthropometric measurements - Sedigheh Yeganeh; Niloofar Motamed; Saeid Najafpour Boushehri; Razieh Bagherzadeh; Maryam Ravanipour (BMC, 2023)
Abstract Background Despite growing awareness of the problem of food security, some areas of Iran continue to experience food insecurity. The aim of the present study was to evaluate maternal performance about food security in dietary diversity for children aged between 12-24 months and its relationship with anthropometric measurements in Bushehr. Methods A cross-sectional study was carried out using 400 mothers of children aged from 12 to 24 months in Bushehr selected via quota sampling. Data were collected using a reliable localized version of a 32-item food frequency questionnaire, consisting of six subscales, with a Cronbach's α: 0.81. The anthropometric measurements of height and weight were also calculated. Data analysis was performed using median, Mean±SD and multinomial logistic regression test, and odds ratio in SPSS, version 18. Results According to standard servings, only 24% of the mothers fed their infants cereals, whereas 54.8%, 36.3%, 39.8%, and 20.3% of the mothers used meat, fruits, vegetables, and dairy products, respectively. The strongest associations were between attendance at educational classes and vegetable consumption (OR=2.09, CI=1.03-4.21), age at the onset of complementary feeding and the consumption of meat (OR=1.30, CI=1.02-1.66) and fruits (OR=1.44, CI=1.03-2.03), and the mothers' level of education and use of dairy products (OR=0.29, CI=0.09-0.90). No evidence of a significant association was found between consumption of any food groups and the anthropometric measurements. Conclusions Mothers in Bushehr performed poorly in providing their infants with the required nutrition with regard to dietary diversity and amount of food. However, their performance can be improved by enhancing their basic nutrition knowledge, holding practical classes on food preparation for them, and focusing on mothers with infants in high-risk groups, e.g. infants suffering from excessive weight gain, obesity, and malnutrition.